Optimal design of THEDES based on Perillyl Alcohol and Ibuprofen - Silva, Eduardo Alexandre Pereira (2020)
Therapeutic deep eutectic systems (THEDES) have dramatically expanded their popularity in the pharmaceutical field due to their ability to increase active pharmaceutical ingredients (APIs) bioavailability. However, their biological performance has not yet been carefully scrutinized. Herein, THEDES based on the binary mixture of perillyl alcohol (POH) and ibuprofen (IBU) were prepared using different molar ratios. Our comprehensive strategy includes the characterization of their thermal and structural behavior to identify the molar ratios that successfully form deep eutectic systems. The in vitro solubility of the different systems prepared has demonstrated that, unlike other reported examples, the presence of the terpene did not affect the solubility of the anti-inflammatory agent in a physiological simulated media. The biological performance of the systems was studied in terms of their antimicrobial activity against a wide panel of microorganisms. The examined THEDES showed relevant antimicrobial activity against all tested microbial strains, with the exception ofÂ P. aeruginosa. A synergistic effect from the combination of POH and IBU as a eutectic system was verified. Furthermore, the cytotoxic profile of these eutectic systems towards colorectal cancer (CRC) in vitro cell models was also evaluated. The results provide the indication that the cell viability varies in a dose-dependent manner, with a selective THEDES action towards CRC cells. With tunable bioactivities in a ratio-dependent manner, THEDES enhanced the antimicrobial and anticancer properties, representing a possible alternative to conventional therapies. Therefore, this study provides foreseeable indications about the utility of THEDES based on POH and IBU as strong candidates for novel active pharmaceutical systems.